Assessing the Needs of Patients with Cancer and Healthcare Professionals for a Digital Pain Management System: A Qualitative Study - Xie X; Gao X; Wang H; Li B; Wang Y; Jiao X; Xv X; Zhou L (Patient Preference and Adherence)
Xiaotong Xie,1,* Xue Gao,2,* Hui Wang,1,* Binghua Li,1 Yan Wang,3 Xiaodong Jiao,3 Xiaowan Xv,4 Lingjun Zhou1 1Faculty of Nursing, Naval Medical University, Shanghai, People’s Republic of China; 2Department of Nursing, No. 943 hospital of the People’s Liberation Army, Wuwei, Gansu Province, People’s Republic of China; 3Oncology Departments, Changzheng Hospital, Shanghai, People’s Republic of China; 4Oncology Departments, Changhai Hospital, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lingjun Zhou, Faculty of Nursing, Naval Medical University, No. 800 Xiangyin Road, Shanghai, 200433, People’s Republic of China, Email zhoulingjun5771@163.comObjective: To understand the willingness of patients and healthcare workers to use, as well as their needs for, an intelligent cancer pain management platform. The findings will serve as a reference for developing cancer pain management tools in China.Methods: A Purposive sampling was used to conduct semi-structured interviews from March to June 2024 with patients experiencing chronic cancer pain, their family members, and healthcare workers in the oncology departments of two tertiary grade A hospitals in Shanghai, China. Data were analyzed using the Colaizzi’s seven-step analysis.Results: The needs of patients and healthcare workers for a cancer pain management app were categorized into five themes, namely, recording of pain status, medication reminders, health education, social support, and artificial intelligence assistance.Conclusion: Future development of an advanced cancer pain management platform must address the multiple challenges currently faced in out-of-hospital cancer pain management, while also considering the needs and preferences of patients and healthcare workers. The platform should integrate features such as visualization of patients’ pain trends, online medical education, peer support, real-time counseling, artificial intelligence assistance, and guidance for at-home self-management and supervision.Keywords: cancer pain, mHealth, pain management, artificial intelligence, needs assessment